Impact of a Transformational Leadership Program for Nurse Managers on Nurses' Job Satisfaction and Work Environment in Saudi Arabian Primary Healthcare Centers: A Quasi-Experimental Study - Alrashidi Nasser Ayidh M; Tukimin bin Sansuwito (F1000Research, 2026)
Abstract* Background Transformational leadership has been associated with improved organizational performance and employee well-being. However, evidence on structured transformational leadership program in primary healthcare settings remains limited, particularly in Saudi Arabia. This study evaluated the effectiveness of a transformational leadership program in improving nurses’ job satisfaction and perceptions of the work environment in primary healthcare centers in Medina, Saudi Arabia. Methods A quasi-experimental pre-test and post-test study with a control group was conducted among 104 nurses working in Ministry of Health primary healthcare centers in Medina, Saudi Arabia. Participants were assigned to an intervention group (n = 52) or a control group (n = 52). The intervention comprised a structured transformational leadership program delivered to nurse managers over two weeks. Job satisfaction was assessed using the Minnesota Satisfaction Questionnaire (MSQ), while the work environment was assessed using the Areas of Worklife Survey (AWS). Within-group changes were examined using paired-samples t-tests, and analysis of covariance (ANCOVA) was used to compare post-intervention outcomes between groups after adjustment for baseline scores. Results Significant improvements were observed in the intervention group compared with the control group across all study outcomes. After adjustment for baseline scores, ANCOVA demonstrated significant intervention effects on overall job satisfaction (partial η 2 = 0.883), intrinsic job satisfaction (partial η 2 = 0.910), extrinsic job satisfaction (partial η 2 = 0.689), and work environment (partial η 2 = 0.747) (all p < 0.001). Conclusions A structured transformational leadership program delivered to nurse managers over two weeks was associated with significant improvements in nurses’ job satisfaction and perceptions of the work environment in primary healthcare centers. Leadership development may provide a practical organizational strategy for strengthening nurses’ workplace well-being and improving work environments in primary healthcare settings.